2012
DOI: 10.1002/etc.1859
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of dietary methylmercury to fish: Derivation of ecologically meaningful threshold concentrations

Abstract: Threshold concentrations associated with adverse effects of dietary exposure to methylmercury (MeHg) were derived from published results of laboratory studies on a variety of fish species. Adverse effects related to mortality were uncommon, whereas adverse effects related to growth occurred only at dietary MeHg concentrations exceeding 2.5 µg g(-1) wet weight. Adverse effects on behavior of fish had a wide range of effective dietary concentrations, but generally occurred above 0.5 µg g(-1) wet weight. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
123
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 150 publications
(131 citation statements)
references
References 74 publications
6
123
1
1
Order By: Relevance
“…Only 2 individual samples of the guitarfish had THg levels (1.74 and ) higher than this limit. However, a recent review on the effect of dietary MeHg on fish indicated adverse effects on reproduction as well as histological, biochemical, and genetic effects at concentrations below 0.2 µg g −1 wet weight (Depew et al 2012). Some samples composed of large individuals of guitarfish, fat snoot, largehead hairtail, Patagonian flounder, and barbel drum from the Santos region had Hg concentrations of that magnitude; however, the health impact on these species at the population level is difficult to assess.…”
Section: Mercury In Organismsmentioning
confidence: 99%
“…Only 2 individual samples of the guitarfish had THg levels (1.74 and ) higher than this limit. However, a recent review on the effect of dietary MeHg on fish indicated adverse effects on reproduction as well as histological, biochemical, and genetic effects at concentrations below 0.2 µg g −1 wet weight (Depew et al 2012). Some samples composed of large individuals of guitarfish, fat snoot, largehead hairtail, Patagonian flounder, and barbel drum from the Santos region had Hg concentrations of that magnitude; however, the health impact on these species at the population level is difficult to assess.…”
Section: Mercury In Organismsmentioning
confidence: 99%
“…As mentioned above, muscle in fish is the main edible part, and it accumulates MeHg (Depew et al, 2012). In largemouth bass, the total mercury concentration in muscle was highly correlated with that of scales (r = 0.89) (Lake et al, 2006), indicating the importance of examining the interaction between mercury exposure and bone metabolism in fish.…”
Section: Introductionmentioning
confidence: 88%
“…Hg 0 has been shown to be oxidized to inorganic mercury (InHg) in aquatic environments, and particularly easily in seawater (Yamamoto, 1996). InHg is convertible to methylmercury (MeHg) in natural environments, and most of the mercury in fish tissue has been reported to be MeHg (WHO, 2008;WHO, 2010;Depew et al, 2012). The toxicokinetics (absorption, distribu-tion, metabolism, and excretion) of mercury are highly dependent on the form of mercury (WHO, 2008;WHO, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…An EQS for biota also automatically accounts for Hg bioavailability issues, thus greatly increasing the possibility to identify situations requiring risk management during routine monitoring programs. Depew et al (2012) derived a threshold concentration of 40 ng g À1 wet weight for reproductive effects in fish following dietary exposure to meHg. Besides protecting piscivorous organisms, the proposed EQS is therefore amenable to application for the protection of prey fish.…”
mentioning
confidence: 99%
“…As to the other possibilities, application of the EQS to invertebrates will protect forage fish against dietary Hg exposure (Depew et al 2012), but EQS for piscivorous wildlife and forage fish may not be interchangeable. Finally, the choice of including Hg in the list of UPBT would shift focus from the national to the global scale, thus reducing efforts to target important local issues.…”
mentioning
confidence: 99%